ANALISIS WACANA TERHADAP PERNYATAAN â€œAKAL SEHATâ€ DI MEDIA SOSIAL (SEBUAH STUDY KASUS PERNYATAAN ROCKY GERUNG) - Hardian, Arvin (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to determine the representation of thoughts and statements of Rocky Gerung about "Common Sense" contained in social media. This study uses the Norman Fairclough model of critical discourse analysis by examining the level of texts, discourse practices, and sociocultural practices. The results of the study at the text level show that GE represents opposition to the government by emphasizing the role of open criticism with the jargon "Common Sense". At the level of discourse practice it is found that RG implements opposition practices in social media using a hierarchical logic writing system. At the socio-cultural level, the GE conducted an effort to trace the digital traces of statements made by the government to become one of the historical sources. However, the discourse from RG is very maintaining the ethics of communication and only expresses the word "Jae" without mentioning who has a role, even though during the five-year journey of the faction called "Cebong and Kampret" both are trying to do a proxy war in social media in order to maintain its existence.